2018
DOI: 10.3390/cells7120273
|View full text |Cite
|
Sign up to set email alerts
|

Tangential Flow Filtration for Highly Efficient Concentration of Extracellular Vesicles from Large Volumes of Fluid

Abstract: Concentration of extracellular vesicles (EVs) from biological fluids in a scalable and reproducible manner represents a major challenge. This study reports the use of tangential flow filtration (TFF) for the highly efficient isolation of EVs from large volumes of samples. When compared to ultracentrifugation (UC), which is the most widely used method to concentrate EVs, TFF is a more efficient, scalable, and gentler method. Comparative assessment of TFF and UC of conditioned cell culture media revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
280
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 316 publications
(284 citation statements)
references
References 44 publications
4
280
0
Order By: Relevance
“…The fluid flows tangentially to the membranes, reducing pore clogging, and leading to more effective separation when compared to conventional (dead‐end) filtration. Notably, TFF is very effective at separating nanosized components from larger (micrometer‐sized and above) and smaller (angstrom‐sized) components,16 but is unable to separate different types of nanoparticles (e.g., EVs and lipoproteins). However, one of the main advantages of TFF is that large volumes (>1 L) can be processed for scalable manufacturing, whereas other EV isolation techniques, such as size‐exclusion chromatography (SEC), are limited by much smaller input volumes 26–28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fluid flows tangentially to the membranes, reducing pore clogging, and leading to more effective separation when compared to conventional (dead‐end) filtration. Notably, TFF is very effective at separating nanosized components from larger (micrometer‐sized and above) and smaller (angstrom‐sized) components,16 but is unable to separate different types of nanoparticles (e.g., EVs and lipoproteins). However, one of the main advantages of TFF is that large volumes (>1 L) can be processed for scalable manufacturing, whereas other EV isolation techniques, such as size‐exclusion chromatography (SEC), are limited by much smaller input volumes 26–28.…”
Section: Resultsmentioning
confidence: 99%
“…However, one of the main advantages of TFF is that large volumes (>1 L) can be processed for scalable manufacturing, whereas other EV isolation techniques, such as size‐exclusion chromatography (SEC), are limited by much smaller input volumes 26–28. TFF also results in higher batch‐to‐batch consistency compared to conventional methods, such as ultracentrifugation 16. Moreover, standard testing for bacteria, mycoplasma, and endotoxin has previously demonstrated that sterility can be maintained throughout the process (from lipoaspiration to obtaining the final product with TFF),16 which is an important aspect for clinical translation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations